Chronic neuropathological and neurobehavioral changes in a repetitive mild traumatic brain injury model. Issue 2 (20th February 2014) - Mouzon, Benoit C.; Bachmeier, Corbin; Ferro, Austin; Ojo, Joseph‐Olubunmi; Crynen, Gogce; Acker, Christopher M.; Davies, Peter; Mullan, Michael; Stewart, William; Crawford, Fiona
<x xml:space="preserve">Abstract</x> Objective Traumatic brain injury (TBI) is a recognized risk factor for later development of neurodegenerative disease. However, the mechanisms contributing to neurodegeneration following TBI remain obscure. Methods In this study, we have utilized a novel mild TBI (mTBI) model to examine the chronic neurobehavioral and neuropathological outcomes following single and repetitive mTBI at time points from 6 to 18 months following injury. Results Our results reveal that at 6, 12, and 18 months after injury, animals exposed to a single mTBI have learning impairments when compared to their sham controls without exhibiting spatial memory retention deficits. In contrast, animals exposed to repetitive injury displayed persistent cognitive deficits, slower rate of learning, and progressive behavioral impairment over time. These deficits arise in parallel with a number of neuropathological abnormalities, including progressive neuroinflammation and continuing white matter degradation up to 12 months following repetitive injury. Neither single nor repetitive mTBI was associated with elevated brain levels of amyloid beta or abnormal tau phosphorylation at 6 or 12 months after injury. Interpretation Importantly, these data provide evidence that, although a single mTBI produces a clinical syndrome and pathology that remain static in the period following injury, repetitive injuries produce behavioral and pathological changes that continue to evolve many months after the initial injuries. As such, this model recapitulates many aspects described in human studies of TBI, providing a suitable platform on which to investigate the evolving pathologies following mild TBI and potential strategies for therapeutic intervention. ANN NEUROL 2014;75:241–254